Automatic transmission fluid corrosion inhibitor interactions with copper. (19th July 2018) - Warren, Bethan; Hunt, Gregory J.; Bryant, Michael; Neville, Anne; Morina, Ardian; Gahagan, Michael
Abstract: In this paper, a new method, measuring the change in resistance of a thin copper wire, has been applied to provide a way to monitor a corrosion reaction in situ. Two different corrosion inhibitors used in commercial automatic transmission fluids have been studied at 110 °C, 120 °C, 130°C, and 150 °C using this new test method coupled with a more traditional coupon test to allow surface analysis to be carried out. Both inhibitors were found to be equally as effective up to temperatures of 130°C; however, the evidence provided shows that at 150°C, the thiadiazole inhibitor is breaking down leading to severe pitting on the surface. Corrosion performance therefore, cannot be assumed to be effective at all temperatures, and the current method provides a convenient quantitative screening method for inhibitor evaluation.